Modality of Strengthening Cooperation Relationship Riau Island (Indonesia) with Terengganu (Malaysia) - Anastasia Wiwik Swastiwi; Herry Wahyudi; Rizqi Apriani Putri; Sayed Fauzan Riyadi; Wanofri Samry; Vioni Dwi Saswi; Linggo Prabowo (Jurnal Ilmu Sosial dan Humaniora, 2023)
Historical and cultural backgrounds mutually influence the cooperation between the Riau Islands (Indonesia) and Terengganu (Malaysia). The relationship between the Riau Islands (Indonesia) and Terengganu (Malaysia) leaves cultural heritage such as manto hoods, copper household items, gamelan, and others. Close relations between the two can be enhanced in cooperation through cultural diplomacy and public diplomacy. This research uses historical research methods with cultural and public diplomacy theories. The study results show that the modality for strengthening the cooperation relations between the Riau Islands (Indonesia) and Terengganu (Malaysia) is in the socio-cultural and economic field. Therefore, each country always has the same socio-cultural strength and the opportunity to develop the economic potential of the existing historical and cultural heritage.